2010
DOI: 10.1007/s10661-009-1301-2
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring changes in soil organic carbon pools, nitrogen, phosphorus, and sulfur under different agricultural management practices in the tropics

Abstract: Soil organic matter not only affects sustainability of agricultural ecosystems, but also extremely important in maintaining overall quality of environment as soil contains a significant part of global carbon stock. Hence, we attempted to assess the influence of different tillage and nutrient management practices on various stabilized and active soil organic carbon pools, and their contribution to the extractable nitrogen phosphorus and sulfur. Our study confined to the assessment of impact of agricultural mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 37 publications
3
15
0
Order By: Relevance
“…This is consistent with observations by Blair et al (2006) and Rudrappa et al (2006). Similar concentrations of KMnO 4 C following manure and straw amendments have also been reported under wheat-maize and rice-wheat systems by Verma et al (2010), and are probably related to the similar amounts of lignin supplied in the SNPK and MNPK treatments because the KMnO 4 C content of organic materials (straw and manure) do not correlate with their total C contents but significantly correlate with their lignin contents (Tirol-Padre and Ladha, 2004). In addition, Blair et al (2006) observed similar KMnO 4 C contents in chemically fertilized and unfertilized soils.…”
Section: Kmno 4 -Oxidizable Carbon and The Carbon Management Indexsupporting
confidence: 93%
“…This is consistent with observations by Blair et al (2006) and Rudrappa et al (2006). Similar concentrations of KMnO 4 C following manure and straw amendments have also been reported under wheat-maize and rice-wheat systems by Verma et al (2010), and are probably related to the similar amounts of lignin supplied in the SNPK and MNPK treatments because the KMnO 4 C content of organic materials (straw and manure) do not correlate with their total C contents but significantly correlate with their lignin contents (Tirol-Padre and Ladha, 2004). In addition, Blair et al (2006) observed similar KMnO 4 C contents in chemically fertilized and unfertilized soils.…”
Section: Kmno 4 -Oxidizable Carbon and The Carbon Management Indexsupporting
confidence: 93%
“…4D) due to accumulation of phosphorus in the crop field for longer period of cultivation. High level of available P was also reported by Verma et al [29] for soils of IARI farm. The delineated map showed presence of medium level (4.5-11.2 mg kg -1 ) of available P in the south and south-eastern corner of IARI farm.…”
Section: Spatial Distribution Of Soil Properties and Its Managementsupporting
confidence: 75%
“…Sustainable yield index reflects the stability of yield with different management practices withstanding variations of rainfall and other climatic conditions. A balanced application of plant nutrients, organic amendments, and inclusion of legumes can enhance and sustain SOC concentration and stock (Majumder et al, 2007; Mandal et al, 2008; Verma et al, 2010; Srinivasarao et al, 2011).…”
mentioning
confidence: 99%